Accuracy analysis on access hyper-point real-time detection algorithms in high-speed network - Haiqing YU; Wei DING; Jie XU (Dianxin kexue)
Real-time access hyper-point helps managers better control the network.Under high-speed network conditions,the difficulty in accessing hyper-point detection lies in the pressure exerted by large traffic on computing.Based on the 40 Gbit/s bandwidth network environment,from the perspective of accuracy analysis,the flow record statistics algorithm and the estimation-based superpoint detection algorithm were compared.The flow record statistical algorithm was improved by the threshold model based on heavy-tailed distribution.The estimation-based superpoint detection algorithm was implemented in the GPU environment by SRLA.The research results show that the estimation-based hyper-point detection algorithm which has obviously higher accuracy and more room for improvement is more suitable for real-time detection of hyper-point in high-speed network than the flow record statistical algorithm.